2020
DOI: 10.3390/jrfm13020037
|View full text |Cite
|
Sign up to set email alerts
|

An Ensemble Classifier-Based Scoring Model for Predicting Bankruptcy of Polish Companies in the Podkarpackie Voivodeship

Abstract: This publication presents the methodological aspects of designing of a scoring model for an early prediction of bankruptcy by using ensemble classifiers. The main goal of the research was to develop a scoring model (with good classification properties) that can be applied in practice to assess the risk of bankruptcy of enterprises in various sectors. For the data sample, which included 1739 Polish businesses (of which 865 were bankrupt and 875 had no risk of bankruptcy), a genetic algorithm was applied to sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 60 publications
2
18
0
Order By: Relevance
“…AUC and accuracy for the training model are 98 and 89% and for testing models are 96 and 86%. Several previous studies also found these consistent results (Heo, 2014; Kim and Kang, 2010; Pisula, 2020). Consequently, this indicates that the ensemble classifier can be used for financial solvency prediction.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…AUC and accuracy for the training model are 98 and 89% and for testing models are 96 and 86%. Several previous studies also found these consistent results (Heo, 2014; Kim and Kang, 2010; Pisula, 2020). Consequently, this indicates that the ensemble classifier can be used for financial solvency prediction.…”
Section: Resultssupporting
confidence: 83%
“…After selecting the model training and testing, all model performances are measured. This study found that the ANNC is the best model for financial solvency prediction among all model, EC also has consistent results (Heo, 2014;Kim and Kang, 2010;Pisula, 2020;Ioannidis et al, 2010;Kim and Kang, 2010;Yeh et al, 2010;Olson et al, 2012).…”
Section: Implication and Conclusionsupporting
confidence: 71%
See 1 more Smart Citation
“…Brozyna et al [37] or Sivasankar et al [82] show that the CART performs better than k-NN. Research by Adamko and Siekelova [83] and Pisula [84] show that ensemble models, whether boosting or bagging, are achieving even higher accuracy and more valuable results. Hence, the weight of the main element was present to the highest proportion.…”
Section: Model Composition and Settingsmentioning
confidence: 99%
“…According to Agarwal and Taffler (2008), there is little difference in the predictive ability of prediction methods in the UK. Similar research can be orientated to differences in other countries, such as in the research of Fedorova et al (2013), Kristof and Virag (2020), Pisula (2020), Kovacova et al (2019), etc. Due to the aforementioned studies, this paper contributes to the literature in the area of evaluation of the mining industry, in addition to its connection with other industries, and compares the possibility of mining conditions in various regions and countries.…”
Section: Literature Reviewmentioning
confidence: 99%